Why Does Cargo Spend Weeks in Sub-Saharan African Ports? Lessons from Six Countries - Raballand, Gaël; Refas, Salim; Beuran, Monica; Isik, Gözde (Washington, DC: World Bank, 2013)
This study is timely because several investments are planned for container terminals in Sub-Saharan Africa. From a public policy perspective, disentangling the reasons behind cargo delays in ports is crucial to understanding:a) whether projects by the World Bank and other donors have addressed the most salient problems; and b) whether institutional port reform and infrastructure, sometimes complemented by customs reform, are the most appropriate approaches or should be adapted. Without such identification and quantification, projects may ultimately result in a limited impact, and structural problems of long delays will remain. Dwell time figures are a major commercial instrument used to attract cargo and generate revenues. Therefore, the incentives for a port authority and a container terminal operator are increasingly strong to lower the real figure to attract more cargo. At the same time, ports are more and more in competition, so the question of how to obtain independently verifiable dwell time data is increasingly critical to provide assurance that interventions are indeed having the intended effect.